The significance of molecular imaging for MRI in neuroradiology - Heckl, S; Pipkorn, R; Nägele, T; Küker, W; Voigt, K (2003)
Molecular imaging with magnetic resonance imaging (MRI) is currently mainly focussed upon the representation of gene expression, the delineation of cell compartments, cell tracking and the display of extracellular structures. The majority of these methods are still at an experimental stage. The main points of interest in neuroradiology are the differentiation between tumor and non-tumor cells with the aid of oncogene profiles, the tracking of transplanted oligodendrocyte progenitor cells for the determination of the extent of remyelinization in the spinal cord and also the assessment of the therapeutic success in apoplexy using subventricular zone cells. New gadolinium contrast agents have enabled the depiction of β-amyloid plaques in Alzheimer's disease as well as showing the distribution of the endothelial leukocyte receptor ICAM-1 in acute experimental allergic encephalomyelitis (EAE).